Structural and mechanical properties of Cu-SiCp nanocomposites fabricated by accumulative roll bonding (ARB) - Ghaderi, Omid; Zare, Mehran; Sadabadi, Hamed; Toroghinejad, Mohammad Reza; Najafizadeh, Abbas; Church, Benjamin C.; Rohatgi, Pradeep K. (Frontiers in Materials, 2024)
In this study, the accumulative roll bonding (ARB) method, a severe plastic deformation (SPD) process, was used to fabricate copper-2 wt% silicon carbide composite strips. The ARB process was successfully conducted for up to nine cycles on pure copper strips with silicon carbide particles distributed between them, as well as on monolithic copper. Equiaxed tensile and Vickers hardness tests were conducted to evaluate the mechanical properties of the samples. SEM was utilized to study the fracture surfaces and to determine the fracture mechanism of ARB processed monolithic copper and composite samples after the tensile test. Texture parameters were calculated through X-ray analysis. The Rietveld method using MAUD software were employed to assess the crystallite size of the samples. Results indicated that average amount of porosity decreased and interface bonding between copper strip layers improved with increasing the number of ARB cycles. Moreover, an increased number of cycles led to homogeneous distribution of SiC particles within the copper matrix. The tensile strength of the fabricated composites improved with an increase in the number of cycles, ultimately reaching 483 MPa after nine cycles, compared to 388 MPa for the composite processed with a single cycle of ARB and 194 MPa for annealed copper strips. Initially, the elongation of the composite samples decreased dramatically to about 6% after applying 5 cycle of ARB process from the 46% observed for annealed pure copper strip. However, it improved as the process continued, reaching 8.9% after the ninth cycle. Investigation of fracture surfaces after the tensile test using SEM revealed that the dominant failure mode was shear ductile fracture. Analysis of sample textures demonstrated that the dominant texture was (100). Crystallite sizes for pure copper and nine cycles-rolled composites, as determined by Reitveld method, reached 111 nm and 89 nm, respectively.